Invisible and everywhere: Heterosexuality in anti-pornography feminism. (September 2015) - Thompson, Jay Daniel
This article investigates the various (and curiously under-theorised) ways in which heterosexuality is framed in anti-pornography feminist discourses. I argue that within these discourses, a certain model of patriarchal heterosexuality is understood as providing the basic framework for all material classified as 'pornography', even that which is produced by and for queers. At the same time, though, the term 'heterosexuality' rarely appears within these discourses. To this end, I argue that anti-pornography feminism risks naturalising the heterosexualised gender hierarchy that its proponents have so vehemently opposed. I suggest that critiquing this aspect of anti-pornography feminism is a crucial step in working towards a theory of heterosexuality which does not deny the existence of sexism, but which also emphasises transgression.